Podoplanin Drives Motility of Active Macrophage via Regulating Filamin C During Helicobacter pylori Infection - Cheok, Yi Ying; Tan, Grace Min Yi; Fernandez, Keith Conrad; Chan, Yee Teng; Lee, Chalystha Yie Qin; Cheong, Heng Choon; Looi, Chung Yeng; Vadivelu, Jamuna; Abdullah, Suhailah; Wong, Won Fen (Frontiers in Immunology, 2021)
Podoplanin (Pdpn) is a mucin–type transmembrane protein that has been implicated in multiple physiological settings including lymphangiogenesis, platelet aggregation and cancer metastasis. Here, we reported an absence of Pdpn transcript expression in the resting mouse monocytic macrophages, RAW264.7 cells; intriguingly, a substantial upregulation of Pdpn was observed in activated macrophages following Helicobacter pylori or lipopolysaccharide stimulation. Pdpn–knockout macrophages demonstrated intact phagocytic and intracellular bactericidal activities comparable to wildtype but exhibited impaired migration due to attenuated filopodia formation. In contrast, an ectopic expression of Pdpn augmented filopodia protrusion in activated macrophages. NanoString analysis uncovered a close dependency of Filamin C gene on presence of Pdpn, highlighting an involvement of Filamin C in modulation of actin polymerization activity which controls cell filopodia formation and migration. In addition, interleukin–1β production was significantly declined in the absence of Pdpn, suggesting a role of Pdpn in orchestrating inflammation during H. pylori infection besides cellular migration. Together, our findings unravel the Pdpn network that modulates movement of active macrophages.